Commitment of High-quality Human resources in State-owned enterprises: An integrative review of mechanisms and determinants - Do Thi Y Nhi,; Nguyen Van Chien,; Nguyen Thi Quynh Nga, (Technium Social Sciences Journal, 2026)
In the context of deepening global economic integration and intensifying talent competition, the retention of high-quality employees has become a strategic challenge for state-owned enterprises (SOEs) worldwide. Operating as hybrid organizations that combine public governance mandates with market-oriented performance logics, SOEs constitute a complex institutional setting in which similar human resource management (HRM) practices often generate divergent forms of organizational commitment. Drawing on an interdisciplinary perspective at the intersection of HRM, organizational psychology, institutional governance, and sustainability-oriented management, this article conducts an integrative review of 73 peer-reviewed studies published between 2000 and 2025, following PRISMA 2020 guidelines. Through thematic synthesis and theory mapping, the review identifies core theoretical tensions among motivation-based perspectives, social exchange under constrained reciprocity, psychological empowerment, and the three-component model of organizational commitment. The findings demonstrate that HRM practices do not exert uniform effects on affective, continuance, and normative commitment, particularly in contexts characterized by high institutional stability and limited managerial discretion. Building on these insights, the article proposes an integrative conceptual framework that positions psychological empowerment as a context-conditioned micro-level mechanism linking HRM practices to differentiated commitment outcomes in hybrid SOEs. By recontextualizing social exchange and commitment theories within public and hybrid organizational settings, this study advances multidisciplinary scholarship and offers a foundation for developing sustainable HRM strategies aimed at retaining high-quality human resources in SOEs.